Novel high Curie temperature Ba2ZnSi2O7 ferroelectrics with low-permittivity microwave dielectric properties. Issue 14 (1st November 2016) - Zou, Zheng-Yu; Lan, Xue-Kai; Lu, Wen-Zhong; Fan, Gui-Fen; Wang, Xiao-Hong; Wang, Xiao-Chuan; Fu, Ping; Lei, Wen
Abstract: Ba2 ZnSi2 O7 ceramics with a monoclinic structure ( C 2/c ) were prepared using the conventional solid-state method at 1200 °C for 3 h in air. The as-prepared ceramics show signs of weak ferroelectricity from the P - E loop and ferroelectric domains with 90° and 103° directions. Although an ε r anomaly appears at approximately 510 °C, the Curie temperature ( T c ) of the Ba2 ZnSi2 O7 ceramics is 750 °C or higher. The ceramics also display low-permittivity microwave dielectric properties ( ε r =8.09, Q × f =26, 634 GHz, and τ f =−51.46 ppm/°C). Therefore, the coexistence of high- T c ferroelectricity and good microwave dielectric properties is beneficial to develop Ba2 ZnSi2 O7 ceramics into tunable-microwave and millimeter-wave devices such as capacitors, phase shifters, and oscillators.